Identification of genetic variants in HSF1 gene and their association with heat tolerance in Murrah buffaloes - SAIKIA, J; VERMA, A; GUPTA, I D; SINGH, S; HAZARIKA, D (The Indian Journal of Animal Sciences, 2019)
The study was carried out to identify Single Nucleotide Polymorphism (SNPs) and their association with thermostolerance traits in 200 murrah Buffalos. Genomic DNA was extracted from frozen/thawed blood samples collected in Beckton-Dickinson vacutainer containing 0.5% (10 Î¼l/ml of blood) anticoagulant EDTA, using phenol-chloroform extraction method. Further the samples were processed for checked quality of DNA on 0.8% agarose gel electrophoresis while its quantification was done using Biospec-nano spectrophotometer method. Custom sequencing results revealed 7 SNPs at the position of A15732G located in intron 4, C17061T in intron 6, C17202T and A17226G in intron 7, G17454A in intron 8, C17605T in exon 9 and T18421C in intron 9 of HSF1 gene sequence. Association analysis showed that the thermal tolerance trait in Murrah buffaloes was significantly affected by three SNP locus, viz. A15732G, C17061T and T18421C. The association among the different genotype of this SNP locus with thermo-tolerance was analyzed using Generalized Linear Model procedure in Statistical Analysis System. Animals of GG genotype at locus A15732 G, TT genotype at locus T18421C and C17061T locus showed lower respiration rate and least HTC was observed in animals belonging to GG genotype at locus A15732G. At linkage, disequilibrium and haplotype construction were analysed using SHEsis software. Haplotypes (49) were constructed, and out of these seven haplotypes (>3 sample size) were considered for association studies. The individuals with Hap6 (ACCAGCC) haplotype combination had lower respiration rate (RR) than other haplotype combinations and these individuals may have better thermal adaptability in comparison to others animals.